2017
DOI: 10.1155/2017/4654803
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided versus Fluoroscopy-Guided Deep Cervical Plexus Block for the Treatment of Cervicogenic Headache

Abstract: Objective. The aim of this study was to compare the efficacy of ultrasound-guided deep cervical plexus block with fluoroscopy-guided deep cervical plexus block for patients with cervicogenic headache (CeH). Methods. A total of 56 patients with CeH were recruited and randomly assigned to either the ultrasound-guided (US) or the fluoroscopy-guided (FL) injection group. A mixture of 2–4 mL 1% lidocaine and 7 mg betamethasone was injected along C2 and/or C3 transverse process. The measurement of pain was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, if ansa cervicalis also has an afferent neuronal composite [ 50 ], the deep CPB would have more clinical significance in treating postoperative pain after neck surgeries involving the infrahyoid and/or SCM muscles, or pain originating in the neck. Wan et al [ 56 ] and Goldberg et al [ 57 ] reported that deep CPBs at the C2 or C3 transverse process could treat cervicogenic headaches effectively. The deep CPB has also been applied during thyroid or parathyroid surgery [ 58 , 59 ], oral and maxillofacial surgery [ 3 ], and CEA [60–64] to obtain adequate anesthesia and/or analgesia.…”
Section: Cervical Plexus Block Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if ansa cervicalis also has an afferent neuronal composite [ 50 ], the deep CPB would have more clinical significance in treating postoperative pain after neck surgeries involving the infrahyoid and/or SCM muscles, or pain originating in the neck. Wan et al [ 56 ] and Goldberg et al [ 57 ] reported that deep CPBs at the C2 or C3 transverse process could treat cervicogenic headaches effectively. The deep CPB has also been applied during thyroid or parathyroid surgery [ 58 , 59 ], oral and maxillofacial surgery [ 3 ], and CEA [60–64] to obtain adequate anesthesia and/or analgesia.…”
Section: Cervical Plexus Block Methodsmentioning
confidence: 99%
“…Deep CPBs can produce major complications such as intravascular injection, epidural or subarachnoid injection, and phrenic nerve palsy, due to its deep endpoint [ 12 , 65 ]; however, with the introduction of ultrasound, the deep CPB has become a relatively safe and simple procedure [ 3 , 42 , 66 , 67 ]. For the ultrasound-guided (USG) deep CPB, Perisanidis et al [ 3 ] and Saranteas et al [ 67 ] simply injected local anesthetics into the space between the prevertebral fascia and the cervical transverse process under ultrasound guidance, but Wan et al [ 56 ] and Sandeman et al [ 66 ] injected local anesthetics after the needle touched the target cervical transverse process under ultrasound guidance.…”
Section: Cervical Plexus Block Methodsmentioning
confidence: 99%
“…A randomized controlled study by Goldberg et al [ 21 ] and non-randomized study by Wan et al [ 22 ] demonstrated effective pain relief following deep cervical plexus block. A retrospective study by He et al [ 23 ] showed significant pain reduction following continuous cervical epidural block for at least 6 months in CeH patients.…”
Section: Resultsmentioning
confidence: 99%
“…The injection effectiveness was rated at 42% effective for all first injections and 40% effective for the last injection. Wan et al [ 22 ] evaluated 56 patients who underwent either an ultrasound-guided or fluoroscopic-guided deep cervical plexus block along the C2 and/or C3 transverse process and reported a significant decrease in pain intensity (NRS) in both groups at 2, 12, and 24 weeks post-injection, with no significant differences observed between the groups. However, the small sample size and lack of double-blinding limited the strength of these findings and a clear understanding of the role of this treatment for CeH management [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, sonography was used to guide transforaminal PRP and steroid injection. The outcomes of nerve root block under the guidance of sonography have proven to be similar to those of injections being guided by either computed tomography scan or X-ray [ 34 36 ]. Furthermore, sonography provides the advantages of real-time and dynamic observation with high accuracy, safe, convenient, no radiation, and avoidance of nerve or vessel injury.…”
Section: Discussionmentioning
confidence: 99%